2020
DOI: 10.1101/2020.04.24.20073296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergency Medical Services resource capacity and competency amid COVID-19 in the United States: Preliminary findings from a national survey

Abstract: This study aimed to investigate available resources, Personal Protective Equipment (PPE) availability, sanitation practices, institutional policies, and opinions among EMS professionals in the United States amid the COVID-19 pandemic using a self-report survey questionnaire. METHODS An online 42-question multiple choice survey was randomly distributed between April 1, 2020, and April 12, 2020 to various active Emergency Medical Services (EMS) paid personnel in all 50 U.S. states including the Distric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Perhaps this is the result of the initial shortage of personal protective equipment for EMS personnel 18 . In one nationally representative survey, many EMS personnel reported limited access to personal protection equipment, with nearly one-third reporting having to reuse the same mask for ≥1 week 18 . By the time mask production increased in the United States, it is possible that EMS personnel believed that they had already been exposed to the virus because of the lack of proper protective equipment in the early stages of the pandemic, ultimately decreasing over time their motivation to wear masks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps this is the result of the initial shortage of personal protective equipment for EMS personnel 18 . In one nationally representative survey, many EMS personnel reported limited access to personal protection equipment, with nearly one-third reporting having to reuse the same mask for ≥1 week 18 . By the time mask production increased in the United States, it is possible that EMS personnel believed that they had already been exposed to the virus because of the lack of proper protective equipment in the early stages of the pandemic, ultimately decreasing over time their motivation to wear masks.…”
Section: Discussionmentioning
confidence: 99%
“…Only three of every four EMS personnel reported always or almost always wearing a mask when outside the house, compared with 100% of HCWs. Perhaps this is the result of the initial shortage of personal protective equipment for EMS personnel 18 . In one nationally representative survey, many EMS personnel reported limited access to personal protection equipment, with nearly one-third reporting having to reuse the same mask for ≥1 week 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing outbreak of the coronavirus disease 2019 (Covid‐19) has caused overwhelming disruptions to healthcare systems around the globe, 1‐4 especially the emergency medical services (EMS). Researchers have conducted extensive studies on different aspects of the EMS since the outbreak of Covid‐19, including the temporal distribution of EMS demand and emergency department visits, 5‐17 pre‐hospital patient assessment, 18,19 medical resource availability and allocation, 20‐23 personnel protective equipment, 24‐26 EMS response practices and strategies 14,27‐29 and ethical considerations 30,31 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that compliance is higher among conservatives [ 11 , 12 , 13 ]; groups with higher income [ 9 ]; people with higher physical fitness; people with a greater perceived risk of the virus [ 14 , 15 , 16 , 17 ]; people with higher values of social responsibility, social trust, and lower self-interest [ 17 ]; and people with higher moral obligation [ 18 ]. Since the COVID-19 pandemic continues to spread, the importance of social distancing is unlikely to change until effective treatments and vaccines become widely available [ 3 , 19 ]. Cellular mobile data revealed that as soon as COVID-19 cases were observed, voluntary compliance improved, but two weeks later, the improvement stopped despite the rise in COVID-19 cases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%